Perilaku Bullying Verbal Pada Peserta Didik Kelas VIII dan IX SMP Negeri 3 Satu Atap Bojong - Nasikhatun Nafisah; Mazro Atus Saadah; Putri Anggriani (La-Tahzan: Jurnal Pendidikan Islam, 2023)
This research is about Verbal Bullying Behavior in Class IX Students of SMP Negeri 3 Satu Atap Bojong. The problem formulations in this study are: (1) what causes individuals to be verbally bullied? (2) what is the impact of verbal bullying on the victim? (3) what is the impact of verbal bullying on the perpetrator? (4) what are the efforts of counseling teachers in dealing with victims of verbal bullying? (5) what are the efforts of counseling teachers in preventing verbal bullying committed by students? This study aims to describe and find out about the forms of verbal bullying behavior that occur in class IX students of SMP Negeri 3 Satu Atap Bojong. quite low category. (1) Family factors as the main cause of individuals committing verbal bullying with the category "quite low" (2) Loneliness which is considered as an act of verbal bullying is "quite low" (3) The highest impact for perpetrators of verbal bullying will be expelled from school with a percentage of 66% with the category "quite". (4) The counseling teacher's effort to prevent verbal bullying with the highest percentage of 71% is to create an asocial context with a "high enough" category. (5) The counseling teacher's efforts in overcoming victims of verbal bullying are "quite high" with a percentage of 67% by working with the school and parents. The method in this study is a qualitative method with data collection techniques, namely by interviewing or observing SMP Negeri 3 Satu Atap Bojong.